On Jesus Christ as Mediator of creation - Conradie, Ernst (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This contribution offers reflection on two of Dirkie Smit’s conversation partners, namely Herman Bavinck and Karl Barth. It notes that both are deeply Trinitarian theologians, but also that such a Trinitarian approach has to address a number of underlying difficulties with respect to the work of the Father, Son and Holy Spirit. On this basis the distinct positions of Bavinck and Barth on the relationship between Christ and creation is explored. Both would confirm that Jesus Christ is the “Mediator of creation” but adopt different approaches in this regard. Such underlying differences are explored and highlighted with the help of GC Berkouwer’s attempt to mediate between these approaches. The essay concludes with the observation that Smit’s emphasis on the centrality of the resurrection may suggest a critical correction to discourse on “Christ and creation”.